Renewable energy for agri-food systems : towards the sustainable development goals and the Paris agreement (International Renewable Energy Agency ; Food and Agriculture Organization of the United Nations, 2021)
Energy and agri-food systems are deeply connected. Agri-food systems consume about 30% of the world's energy. While, energy is responsible for a third of agri-food systems' emissions. A joint approach to the Energy Transition and Food Systems Transformation is therefore essential to meet current and future demand for food and energy in an inclusive and environmentally sustainable manner. Renewable energy solutions represent a crucial opportunity to meet the energy needs in the agriculture sector that are key to raising farmer incomes, cutting losses, creating jobs, improving access to clean cooking fuels, and advancing climate action for mitigation and adaptation. This report jointly developed by the International Renewable Energy Agency and the Food and Agricultural Organization of the United Nations analyses the role of renewable energy in agri-food systems and the opportunity they offer to advance energy and food security objectives as well as contribute to the achievement of the Sustainable Development Goals and the Paris Agreement.